KARAKTERISTIK KAPABILITAS INOVASI USAHA KECIL DAN MENENGAH DI SEMARANG - Eny Rahmani; Siyamtinah Siyamtinah (Jurnal Ekonomi dan Bisnis, 2011)
This research aims to know how the owners of Small Medium Enterprise (SME) develop theirinnovation capacity. Besides that, are there impact of differentiaton in developing innovationcapacity to SME’s operational performance.To answer that questions descriptive statistics was used to explain the first question, and thenwe used ANOVA analysis to answer the second question. Sample in this research is the owneror manager of SME. Using purposive random sampling, we got 100 SME.The result of descriptive statistics show there are 6 design indeveloping innovation capacity andthe differentiation of them have no impact to SME’s operational performance.Keywords : kapabilitas inovasi, kinerja operasional